Electrocardiographic, hemodynamic, and biochemical evidence on the protective effects of exenatide against phosphine-induced cardiotoxicity in rat model. (December 2021) - Bameri, Behnaz; Armandeh, Maryam; Baeeri, Maryam; Haghi-Aminjan, Hamed; Rahimifard, Mahban; Hassani, Shokoufeh; Hooshangi Shayesteh, Mohammad Reza; Samadi, Mahedeh; Gholami, Mahdi; Nayebpour, Mohsen; Ostad, Seyed Nasser; Abdollahi, Mohammad
Aluminum phosphide (AlP) poisoning can be deadly in most cases targeting the heart. To overcome AlP toxicity, exenatide has been studied in the present study due to its pleiotropic effects on cardiac damages. In this study, the rats were exposed to LD50 of AlP (10 mg/kg) by gavage, and exenatide at doses (0.05, 0.1, and 0.2 mg/kg) injected intraperitoneally 30 min after poisoning. The cardiac parameters including heart rate (HR), blood pressure (BP), QRS, corrected QT (QTc ), and ST were monitored for 180 min. Blood glucose level was measured in the study groups 30 min after exenatide injection. Evaluation of biochemical parameters including mitochondrial complexes I, II, and IV activities, adenosine diphosphate (ADP)/adenosine triphosphate (ATP) ratio, malondialdehyde (MDA), apoptosis, lactate, troponin I, and brain natriuretic peptide (BNP) was done on heart tissues after 12 and 24 h. Additionally, the tissues were analyzed for any pathological damages including necrosis, hemorrhage, or hyperemia 24 h post-treatment. Our results showed that AlP-induced HR, BP, and electrocardiographic changes were improved by exenatide at all doses. The blood glucose levels of poisoned animals reached control levels after exenatide treatment. Besides, treatment with exenatide at all doses improved complexes I and IV activity, ADP/ATP ratio, and apoptosis. Malondialdehyde, lactate, troponin I, and BNP levels were also diminished after exenatide co-treatment in poisoned animals. On the other hand, administration of exenatide doses improved the histopathology of AlP-induced tissues. Based on our findings, exenatide has a protective effect against phosphine-induced cardiotoxicity in an almost dose-dependent way. However, further investigations are needed on the potential clinical use of exenatide in this poisoning.